PENGARUH PEMBERIAN URIN KAMBING DAN PUPUK BOKASHI TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Fahmi, M. Nurul; Syafrinal, Syafrinal; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research was aimed to determine the effect of interaction between goat’s urine and bokashi fertilizer, and to get the decent dosagein the growth of cocoa seeds. This research was conducted at the experimental station of Agriculture Faculty of Riau University, from september 2016 to january 2017, factorial by using completely randomized design (CRD) method, 3 replicarions, which consist of two factors. The first factor, goat’s urine dosage consisted of 3 levels (0, 50, and 100 ml/polybag) and the second factor, bokashi fertilizer dosage, consisted 3 levels (0, 50 and 100 g/polybag).The parameters observed were seedling height, leaf number, stem diameter, root volume, leaf area, plants dry weight, and  the shoot to root ratio. Observationts of each parameter were analyzed statistically using analysis of variance and Duncan's new multiple range test (DNMRT) level of 5%. The results show that the interactionbetween goat’s urine and bokashi fertilizer has no significant effect on all parameters, and the goat’s urine dosage of (50-100) ml/polybag and bokashi fertilizer dosage of(50-100) g/polybag is thedecent dosage to increase the all parameters. Keywords: goat’s urine, bokashi fertilizer, cocoa.